Transitional Justice as an opportunity for decriminalisation of sexual and gender minorities in The Gambia - GARRIDO, Rui (Revista Jurídica Portucalense, 2025)
The aim of this study is to assess the opportunity offered by Transitional Justice mechanisms in The Gambia for the recognition of violence against LGBT people and to foster a path toward decriminalisation of same-sex intimacy. Under Yayah Jammeh rule, the violence against LGBT as a pattern of persecution and hatred. The State persecution policy placed the country as one of the most intolerant African nations against LGBT people. The outcome of the 2016 Gambian elections changed the course of politics in Gambia, and in 2018 a Truth and Reconciliation Commission was installed to deal with a past of violence and autocracy, in 2018. This article aims to map the developments regarding violence against LGBT people and highlights the importance to include all forms of violence as a healing strategy in transitional justice. Also, it aims to assess how effective may be these mechanisms to decriminalisation of same-sex acts in transitional societies.